HERBARIA AS PATRIMONY: THE CONTRIBUTION OF THE MFS COLLECTION IN THE CONSERVATION OF AMAZONIAN BIODIVERSITY - Leão, Victor Miranda; Lucas, Flavia Cristina Araujo; Gurgel, Ely Simone Cajueiro (Ciência e Natura, 2017)
Herbaria and living collections play an indispensable role of species conservation strategies. The objective of this work was to discuss the formation of the MFS - Profa. Drª. Marlene Freitas da Silva herbarium, at the Universidade do Estado do Pará, with the goals of helping new Brazilian herbaria and motivating educational institutions, professors and students. The processes that involve the creation of a botanical collection as such as establishing partnershipsare, training technicians, curating, processing field data, taking images, and making data available online are described. Presently, MFS has 6083 dried collections, including angiosperms (5111 spp.), bryophytes (863 spp.), lycophytes and ferns (18 spp.) and fungi (91 spp.). In addition, there are associated collections of seedlings (15 spp.), flowers (47 spp.), fruits and seeds (187 spp.), and an ethnobotanical collection (56). The increasing growth of this collection is a resulted of many interdisciplinary studies in botany, that invested resources to work the social and environmental importance with the biodiversity. MFS is an important academic space and reference for researchers and students because it allows botanical material to be identified, and is a resource of historical, sociocultural and economic information about plants of a distinct and unique region in the world.